A Dual-Validation Mobile Attendance Application for Discipline-Oriented Vocational Schools: Development and Evaluation Using the Waterfall - Hasbi Kurnia; Geovanne Farell; Denny Kurniadi; Rizkayeni Marta (Journal of Hypermedia & Technology-Enhanced Learning, 2025)
Manual attendance systems in educational institutions, particularly in highly disciplined environments such as vocational schools with cadet programs, present significant challenges, including inaccuracy, administrative burden, and susceptibility to fraud. This study addresses these issues by designing and developing a secure mobile attendance application for the Android platform. The development process followed the Waterfall software development model, providing a structured framework from requirements analysis through testing. The proposed solution incorporates a dual-validation mechanism combining Quick Response (QR) Codes for session-specific identification with Geolocation technology to verify users’ physical presence within the designated school area. The application supports multiple user roles, including students, teachers, administrators, and parents, and offers automated attendance tracking for daily roll calls and extracurricular activities. It enables teachers to input attendance for in-class sessions manually. Empirical evaluation confirmed that the application effectively mitigates vulnerabilities inherent in the manual system. The dual-validation approach substantially enhances both the integrity and efficiency of the attendance process, offering a reliable and secure tool for monitoring student discipline. This study provides a practical model for integrating accessible digital technologies to strengthen administrative processes in secondary education contexts.